THE ROLE OF VERBAL AND NON-VERBAL COMMUNICATION IN LEARNING FOREIGN LANGUAGE - Docent Ismailov Anvar Rustamovich; Abdiraupova Dilrabo Asror qizi (Scholar Express Journal, 2022)
The aim of the present paper is to analyze non-verbal communication of a native speaker and a second language learner. The main emphasis is put especially on the differences between the non-verbal signals of second language learners and native speakers. The present paper also covers some suggestions for foreign language teachers in order to improve their knowledge of the body language of their learners in the target language and help them to raise awareness of the significance of non-verbal communication in second language discourse.
Keywords: Communication; Second Language; Ambiguous Interpretations; Eye Contact